PEMBUATAN PETA POTENSI AIR TANAH DESA WIBAWAMULYA MENGGUNAKAN PENDEKATAN SISTEM INFORMASI GEOGRAFIS - Sulfiyana, Sulfiyana; Siaga Pangestuti, Rinda; Nadhirah Qintharah, Yuha (An-Nizam, 2024)
The aims of writing this journal is to provide information regarding the distribution of groundwater potential in Wibawamulya village using a GIS approach. Wibawamulya Village is a village that is often affected by drought due to the dry season. People often experience a lack of clean water for their daily needs so they are forced to use low quality water, of course this can have a negative impact on the health of the surrounding community, such as stunting in children. Due to the negative impact on public health, the government needs special attention to overcome this, for example by building clean water facilities for use by local communities. With this, information is needed regarding the distribution of areas that have potential groundwater sources that can be used as locations for the construction of public facilities for clean water facilities. The method of this community service was written using the science and technology diffusion method, the map was made in Wibawamulya Village, then socialization was carried out at the Village Office. The groundwater potential map creation program is an effort to provide information about areas that have abundant groundwater reserves so that they can be utilized optimally to provide reserves for clean water needs during the dry season in Wibawamulya Village. The existence of this groundwater potential map has an impact on the performance of village governments in mitigating drought and efforts to prevent stunting due to lack of access to clean water and poor sanitation.